Case in Kurdish - Gündoğdu, S. (Springer International Publishing, 2022)
This chapter surveys the forms of case marking across the dialects of Kurdish, as represented in the MDKD. Structural and non-structural (semantic) cases are expressed through a range of different exponents: adpositions (pre-, post- and circumpositions), morphological case, and word-order properties. Structural cases are invariably non-adpositional across all dialects, with the major isogloss separating those dialects that make use of the Oblique case, which include all of Northern Kurdish and a few dialects of Central Kurdish, from those that have lost it. The marking of semantic cases is subject to considerable areal variation, following an approximate north/south cline with prepositional marking increasingly dominant in the south. The findings are illustrated with data from the MDKD, supplemented with reference to other major sources. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.